Analysis of Factors Causing Work Accidents in Fishing Groups in Fatubesi Village, Kupang City - Eka Muftiana Rahmawati; Anderias Umbu Roga; Luh Putu Ruliati; Jefri S. Bale; Noorce Christiani Berek (Dinasti International Journal of Education Management And Social Science, 2025)
The informal sector is a sector that is not organized, non-formal and not incorporated, so that its occupational health has not received optimal attention. More than 60% of Indonesia's total population lives in coastal areas with most of the livelihoods as fishermen. The activities of fishermen at sea have a considerable risk, so fishermen are vulnerable to being faced with changing sea conditions. Objective: This study aims to analyze the factors associated with the incidence of work accidents in fishing groups in Fatubesi Village, Kupang City. Methods: This study used a cross sectional quantitative approach. The population was fishermen in Fatubesi village, Kupang City and sampling using simple random sampling technique as many as 89 respondents. Data were collected through interviews using questionnaires and analyzed using chi-square techniques. Results: the results showed that there was a significant relationship between worker motivation and work accidents (p-value 0.002 < 0.05), skill variables with work accidents (P-value 0.000 < 0.05), and unsafe action relationships with work accidents (p-value 0.000 < 0.05). While there is no relationship between the knowledge variable and the Work Accident variable (p-value 0.221 > 0.05), and there is no influence of the Unsafe Environmental Conditions variable on the Work Accident variable, (p-value 0.447 > 0.05) Conclusion: Work accidents are a multifactor interaction that is a reflection of management. The scope of informal workers such as unorganized fishermen needs to consider the role of the government to be able to assist regulations related to occupational accident risk management. There needs to be a shift in the approach to preventing occupational accidents to improve the skills of fishermen, increase safety culture, and improve safety governance.